Plastics - Shepherd, Greg; Ghosn, Margaret (New York : Appleseed Production, 1993)
This program explores the process of polymerization at the molecular level, describes the chemical composition of polystrene and teflon, discusses thermosetting and thermoplastic polymers, and explains the vulcamization of rubber
Casmera, Greg Shepherd ; production, editing, script, Margaret Ghosn
Visual media for college and high school classrooms
Keywords: Plastics; Polymerization; Thermosetting plastics; Thermoplastics